LIPUTAN MEDIA TENTANG POLITISI DAN AKTIVITAS POLITIK PEREMPUAN - Ida, Rachmah (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2013)
This study analyzes the content of the mass media on female politician and their political activisims in Indonesia. Since the movement to fight for the 30% quota of female in the legislature, the women activity in the political space of this country becomes so rife. Number of women in parliament of national and local level has increased significantly. Further the women who were elected as the head of the region (Governors, Mayors and Regents) and deputy head of the region in Indonesia are also experiencing significant growth. The issue is whether this progress was followed by public support, including the supportive mass media? Hence, this research was conducted to answer the problem formulation: Do female politicians in Indonesia and their political activism getting supportive reports? How mass media represents female politicians? What are constructs of language and symbols manufactured by the media related to the existence of female politicians and female political activism? By using the perspective of media cultural studies, this study uses textual analysis method (text message and visual) covered and described the women politicians in Indonesia. Textual analysis is applied on the news and articles published by some online news media during the year 2011, associated with female politicians and political activism. Results of this study suggest that female politicians still represented stereotypically associated with femininity and its position in the domestic sphere. Vision and political orientation of female politicians have not received significant attention from the media